Implementation of packet scheduling algorithms in LTE-Sim (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
In this research paper we have implemented downlink packet scheduling algorithms in LTE-Sim simulation for LTE cellular networks. The implementation includes adding two packet scheduling algorithms (Round Robin and MaxRate). The performance of these algorithms is tested for various types of real time service (video) and non real time service(data) for fixed and mobile users at various speeds 3, and 120Km/h in LTE-Sim simulator. The simulation was setup with varying number of users 120 in fixed boundedregions of 1 km radius.The goal of this project is to study the simulation of Radio Resource Management (RRM) in 4G networks using LTE-Sim. In particular, it focuses on the comprehensive performance testing of packet scheduling algorithms (such as Max Rate, Round Robin, PF, MLWDF, EXP). The paper shows the results of implementing of these algorithms and testing their performance.